Trained murine mesenchymal stem cells have anti-inflammatory effect on macrophages, but defective regulation on T-cell proliferation - Lin, Tzuhua (FASEB J, 2019)
Mesenchymal stem cell (MSC)-mediated immunomodulation affects both innate and adaptive immune systems. These responses to environmental cues, such as pathogen-associated molecular patterns, damage-associated molecular patterns, or proinflammatory cytokines, are crucial for resolution of inflammation, as well as successful tissue healing and regeneration. We observed that intermittent, repeated exposure of MSCs to LPS induced stronger NF-κB activation than singular stimulation. A similar phenomenon, named innate immune memory or trained immunity, has been reported with macrophages. However, the potential regulation of “immune memory” in nonclassic immune cells, such as MSCs, has not been reported. In the current study, we chose IFN-γ plus TNF-α restimulation-induced iNOS expression as a model of MSC activation, because IFN-γ and TNF-α play crucial roles in MSC-mediated immunomodulation. The iNOS expression was enhanced in LPS-trained MSCs, 3 d after a washout period following primary stimulation. LPS-trained MSCs enhanced the anti-inflammatory (arginase 1 and CD206) marker expression, but decreased the proinflammatory marker (TNF-α, IL-1β, iNOS, and IL-6) expression using an MSC-macrophage coculture model. In contrast, LPS-trained MSCs demonstrated a defective regulation on CD4 T-cell proliferation. Mechanistic studies suggested that histone methylation and the JNK pathway are involved in LPS-trained immunomodulation in MSCs. Our results demonstrate differential immunomodulatory effects of trained MSCs on macrophages and T cells. These immunomodulatory consequences are critical, because they will have a major impact on current MSC-based cell therapies.—Lin, T., Pajarinen, J., Kohno, Y., Huang, J.-F., Maruyama, M., Romero-Lopez, M., Nathan, K., Yao, Z., Goodman, S. B. Trained murine mesenchymal stem cells have anti-inflammatory effect on macrophages, but defective regulation on T-cell proliferation.